2019
DOI: 10.1051/0004-6361/201935828
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the galaxy two-point correlation function using a split random catalog

Abstract: The two-point correlation function of the galaxy distribution is a key cosmological observable that allows us to constrain the dynamical and geometrical state of our Universe. To measure the correlation function we need to know both the galaxy positions and the expected galaxy density field. The expected field is commonly specified using a Monte-Carlo sampling of the volume covered by the survey and, to minimize additional sampling errors, this random catalog has to be much larger than the data catalog. Correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…The variance on the random sample counts depends on the number of points in the sample and, thus, we may ask what is the number of random points needed to achieve the same accuracy as in the analytical method. Keihänen et al (2019) showed that the relative variance on RR in a given bin is: (22) with N r the number of random points, and G p , G t terms are (Landy & Szalay 1993):…”
Section: Rr Countsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variance on the random sample counts depends on the number of points in the sample and, thus, we may ask what is the number of random points needed to achieve the same accuracy as in the analytical method. Keihänen et al (2019) showed that the relative variance on RR in a given bin is: (22) with N r the number of random points, and G p , G t terms are (Landy & Szalay 1993):…”
Section: Rr Countsmentioning
confidence: 99%
“…makes use of additional data-random pairs DR. To estimate the correlation function, we therefore need to compute the number of pairs as a function of the separation. To avoid introducing bias in the estimator and to minimise variance, the random catalogue must be much larger than the data catalogue (Landy & Szalay 1993;Keihänen et al 2019). We usually consider that taking at least about 20−50 times more random points than objects in the data is enough to avoid introducing additional variance (e.g., Samushia et al 2012;de la Torre et al 2013;Sánchez et al 2017;Bautista et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several estimators have been proposed to compute the 2PCF (e.g. Peebles & Hauser 1974;Hewett 1982;Davis & Peebles 1983;Landy & Szalay 1993;Hamilton 1993;Keihänen et al 2019), fewer studies have been performed so far for the 3PCF (e.g., Jing & Börner 1998;Szapudi & Szalay 1998;Sosa Nuñez & Niz 2020). Here we will exploit the widely used formulation proposed by Szapudi & Szalay (1998), that provides an unbiased and with minimal variance estimator based on the counting of triplets between the input catalog (that we will label as data catalog, D), and a corresponding random catalog (that we will label as R), constructed to reproduce the geometric distribution of the input catalog, but with zero clustering.…”
Section: Definitionsmentioning
confidence: 99%
“…The random-random pair count RR(r) was found applying the random number generator ran2 by Press et al (1992), using one or two million particles. To speed up the calculation of random-random pairs we split random samples into 10 independent subsamples, as done also by Keihänen et al (2019).…”
Section: Calculation Of Correlation Functionsmentioning
confidence: 99%